Active offer, bilingualism, and organizational culture - Vézina, Sylvain (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, the author approaches active offer from the angle of organizational culture. He presents the results of a survey of health professionals working in Anglophone and Francophone hospital facilities in New Brunswick. The organizational culture of these institutions is discussed in light of research in the sociology of organizations, not as a fate but as a construct, as are the rules of the organizational game (hierarchical relations, job description, collective agreements, and so on). The research reveals the predominance of an organizational culture centred on bilingualism, which leads to a persistent confusion between the notions of active offer and bilingualism. From this point of view, although bilingualism is essential to a high-quality active offer in both official languages, it can also be counter-productive when it comes to introducing a culture that is favourable to active offer. The findings show the emphasis placed on bilingualism is often perceived by unilingual people as a threat to the balance of powers within the system, frequently leading to resistance toward any measure favourable to active offer. Hence, the author suggests the value of a culture of active offer should be articulated in terms of the objectives of safety and high-quality care in the official languages. Key words: health professionals, hospital facilities, organizational culture, bilingualism, active offer, New Brunswick.
Chapter 10